THE ARAB SPRING AND THE LANDSCAPE OF GOVERNANCE IN TUNISIA: TRANSPARENCY, PARTICIPATION, AND ACCOUNTABILITY - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi; Mouad Abderrahmene Kahla (Malikussaleh Social and Political Reviews, 2026)
This study examines the evolution of open government in Tunisia by mapping scholarly literature published between 2011 and 2025, following the country’s accession to the Open Government Partnership. Using bibliometric analysis with VOSviewer, the study analyzes review articles retrieved through Publish or Perish and indexed in Google Scholar, focusing on transparency, public participation, and accountability as core dimensions of open government. The findings identify three dominant thematic clusters—fiscal transparency and access to information, public participation and democratic innovation, and institutional accountability and digital governance—reflecting both global discourse and Tunisia’s post-revolution governance trajectory. The results reveal a shift from exploratory research toward more consolidated analyses of implementation and institutionalization. However, the study highlights a persistent gap between normative commitments and practical outcomes, as transparency and participation have not consistently produced accountability. To address this, the study proposes the Integrated Open Government Nexus, which conceptualizes these dimensions as sequentially and causally linked within an integrated governance system. The study contributes to advancing theoretical understanding and offers policy insights for strengthening open government in transitional contexts.